Assessment of the neutron dose field around a biomedical cyclotron: FLUKA simulation and experimental measurements. Issue 12 (December 2016) - Infantino, Angelo; Cicoria, Gianfranco; Lucconi, Giulia; Pancaldi, Davide; Vichi, Sara; Zagni, Federico; Mostacci, Domiziano; Marengo, Mario
Highlights: A measurement campaign of the neutron ambient dose equivalent has been conducted. Measurements were conducted in marked locations around a PETtrace cyclotron. Different active and passive neutron detectors were used and compared. Experimental measurements were compared against FLUKA Monte Carlo simulations. An excellent agreements between FLUKA simulations and measurements was found. Abstract: In the planning of a new cyclotron facility, an accurate knowledge of the radiation field around the accelerator is fundamental for the design of shielding, the protection of workers, the general public and the environment. Monte Carlo simulations can be very useful in this process, and their use is constantly increasing. However, few data have been published so far as regards the proper validation of Monte Carlo simulation against experimental measurements, particularly in the energy range of biomedical cyclotrons. In this work a detailed model of an existing installation of a GE PETtrace 16.5 MeV cyclotron was developed using FLUKA. An extensive measurement campaign of the neutron ambient dose equivalent H ∗ (10) in marked positions around the cyclotron was conducted using a neutron rem-counter probe and CR39 neutron detectors. Data from a previous measurement campaign performed by our group using TLDs were also re-evaluated. The FLUKA model was then validated by comparing the results of high-statistics simulations with experimental data. In 10 out of 12 measurement locations, FLUKA simulations were in agreement within uncertainties with all the three different sets of experimental data; in the remaining 2 positions, the agreement was with 2/3 of the measurements. Our work allows to quantitatively validate our FLUKA simulation setup and confirms that Monte Carlo technique can produce accurate results in the energy range of biomedical cyclotrons.